Diffracting addicting binaries: An analysis of personal accounts of alcohol and other drug ‘addiction’ - Pienaar, Kiran; Moore, David; Fraser, Suzanne; Kokanovic, R.; Treloar, C.; Dilkes-Frayne, E. (Sage Publications, 2016)
Associated with social and individual harm, loss of control and destructive behaviour, addiction is widely considered to be a major social problem. Most models of addiction, including the influential disease model, rely on the volition/compulsion binary, conceptualising addiction as a disorder of compulsion. In order to interrogate this prevailing view, this article draws on qualitative data from interviews with people who describe themselves as having an alcohol or other drug ‘addiction’, ‘dependence’ or ‘habit’. Applying the concept of ‘diffraction’ elaborated by science studies scholar Karen Barad, we examine the process of ‘addicting’, or the various ways in which addiction is constituted, in accounts of daily life with regular alcohol and other drug use. Our analysis suggests not only that personal accounts of addiction exceed the absolute opposition of volition/compulsion but also that the polarising assumptions of existing addicting discourses produce many of the negative effects typically attributed to the ‘disease of addiction’.